THE IMPACT OF MANUFACTURING CONCENTRATION ON REGIONAL INEQUALITY: A CASE OF REGENCY IN JAVA REGION, INDONESIA - Setyo Tri Wahyudi; Mohd Dan Jantan (Journal of Indonesian Economy and Business (JIEB), 2012)
Concentration of manufacturing is an interesting topic in location of economic activity since manufacturing was the leading sector in the Indonesian economy. The previousstudies demonstrated that firms were localized in major metropolitan areas as well as a set of emerging regions. The paper aim to complement the findings of the previous studiesrelated to geographical concentration of manufacturing industry by exploring the impact of manufacturing concentration on regional inequality in the regency in Java during the 1998-2007. The Theil index and the location quotient index are employed in order to analysis the inequality and the location of manufacturing industry in Java region.The study found that the Theil index shows an increasing trend implying that the inequality of the manufacturing industry within regencies has increase. While, the inequality between regency shows a decreasing trend over the period of observation implying that the manufacturing industry in Java spreads only in several regencies. The location quotient index shows an increasing trend that reveals the economy of some regencies are more dependent in manufacturing industry and at the same time it shows that several new manufacturing areas has emerged in Java.Keywords: concentration, inequality, manufacturing, Java region